Dryad_ECOG_E02209_Nunes et al._2016 - Nunes, Guilherme T.; Mancini, Patrícia L.; Bugoni, Leandro (Dryad Digital Repository, 2016)
Phenotypic data of brown boobies from six colonies along the South Atlantic Ocean; plus latitude, air temperature, and sea surface temperature data.